Strategies Employed by Senior High School Students in Learning General Mathematics - Palumar, Jezrel (Journal of Interdisciplinary Perspectives, 2024)
This study aimed to identify the strategies employed by students in learning General Mathematics during the pandemic and to examine the relationship of these strategies with selected variables. A descriptive-correlational research design was utilized, and systematic sampling was employed to select 126 Grade 12 respondents. Validated questionnaires were used to collect data, and statistical analyses including mean, weighted mean, t-test for independent data, Pearson correlation, Mann-Whitney U Test, Kruskal-Wallis Test, and ANOVA were conducted. The findings revealed that the extent of students’ utilization of metacognitive, cognitive, and collaborative strategies was “high.” Additionally, their academic performance in General Mathematics was found to be at a “satisfactory” level. Further analysis showed that students with outstanding academic standing before the pandemic (a) had a higher extent of utilization of the strategies compared to those with satisfactory and fairly satisfactory standings, and (b) performed better during the pandemic than those with very satisfactory, satisfactory, and fairly satisfactory ratings. However, no significant differences were found in the strategies employed by students when grouped according to sex and strand. Moreover, the extent of strategy utilization did not have a direct relationship with academic performance. These findings suggest a need for further research into additional factors that may influence learning outcomes. Exploring other variables impacting academic success and developing targeted interventions to enhance student performance is recommended.